Приводимость нелинейных почти периодических систем разностных уравнений, заданных па бесконечномерном торе - Самойленко, А.М.; Мартынюк, Д.И.; Перестюк, Н.А. (Український математичний журнал, 1994)
Sufficient conditions of reducibility of the nonlinear system of difference equations x(t+1)=x(t)+ω+P(x(t),t)+λ, to the system y(t+1)=y(t)+ω are found; here, x,ω,λ∈m, and the infinite-dimensional vector function P(x(t),t) is 2πt - periodic in xi(i=1,2,...) and almost periodic in tt with the frequency basis α.